2022
DOI: 10.1155/2022/1571826
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities, Associated Diseases, and Risk Assessment in COVID-19—A Systematic Review

Abstract: It is considered that COVID-19’s pandemic expansion is responsible for the particular increase in deaths, especially among the population with comorbidities. The health system is often overwhelmed by the large number of cases of patients addressing it, by the regional limitation of funds, and by the gravity of cases at subjects suffering from this pathology. Several associated conditions including diabetes, cardiovascular illnesses, obesity, persistent lung condition, neurodegenerative diseases, etc., increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 227 publications
0
27
0
3
Order By: Relevance
“…Data accrued over the last 2 years reported that specific comorbidities are associated with increased risk of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection and worse outcomes with development of increased severity of lung injury and mortality [1] , [2] , [3] , [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Data accrued over the last 2 years reported that specific comorbidities are associated with increased risk of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection and worse outcomes with development of increased severity of lung injury and mortality [1] , [2] , [3] , [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%
“…A single amino acid substitution in the polymerase (F548S) has been shown to be responsible for reduced susceptibility to remdesivir at low levels in Ebola virus infection treated with RDV, and given that remdesivir’s point of action is a structurally analogous region of the SARS-CoV-2 virus polymerase, molecular surveillance of this site in COVID-19 patients is recommended due to the possible risk of resistance [ 18 ]. Moreover, the emergence of de novo mutations of RDV resistance has been observed in treated immunocompromised patients [ 19 , 20 , 21 ]. There are different mechanisms through which the resistance to RDV may arise in SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Indeed, the levels of particular proteins such as chemokines or cytokines are increased in the plasma of patients with obesity due to the secretion of cytokines with inflammatory activity (interleukin‐10, 1 and 6 and tumor necrosis factor‐alpha) from adipocytes. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, obese patients infected with SARS‐CoV‐2 may have a higher mortality rate related to obesity‐related elevated inflammatory cytokines 3 . Indeed, the levels of particular proteins such as chemokines or cytokines are increased in the plasma of patients with obesity due to the secretion of cytokines with inflammatory activity (interleukin‐10, 1 and 6 and tumor necrosis factor‐alpha) from adipocytes 4 …”
Section: Introductionmentioning
confidence: 99%